THE ADDITION OF FRESH GARLIC (Allium sativum L) IN DUCK FEED REDUCES CHOLESTEROL CONTENT OF DUCK EGG - I Nyoman Sukartha Jaya; Ni Ketut Dewi Haryani; Budi Indarsih (Jurnal Kedokteran Hewan, 2018)
The objective of this study to determine the effect of feeding fresh garlic to ducks on decrease the cholesterol level of duck eggs. This study composed of two treatment groups. The duck in the first group (control) was fed local feed without spplemente d with fresh garlic, while in the second group was fed with local feed and supplemented with 50 grams of fresh garlic/duck/day. Egg yolk cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides (TG) analysis were carried out at the end of the study using the ether extract method and then with the Cholesterol Oksidase Para Amino Penazone (CHOD-PAP) or enzymatic color test. Data was analysed using one way Analysis of Variance (ANOVA) the results showed that fresh garlic reduced total cholesterol, LDL fraction, and triglyceride, but increased the HDL fraction of duck egg yolk. The total cholesterol, LDL fraction, and triglyceride of duck egg yolks dropped by around 15.98 mg per dL (8.06%), 10.40 mg per dL (12.97%), 64.92 mg per dL (12.71%), respectively, while the HDL fraction increased by 11.40 mg per dL (19.32%) The results of this study indicated that fresh garlic can be used to produce specific products such as low cholesterol and low fat duck eggs.